1985
DOI: 10.1093/ajcp/83.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Carcinoma: A Study of 70 Cases

Abstract: Seventy cases of anaplastic thyroid carcinomas studied at the Universities of Florence (Italy) and Minnesota are presented. Three morphologic patterns were seen: spindle, giant cell, and squamoid, sometimes in combination. Ultrastructurally, evidence of epithelial differentiation was seen in most but not all cases studied. Immunohistochemically, a stain for cytokeratin using a monoclonal antibody was found the most useful adjunct to diagnosis. Unexpected positivity for carcinoembryonic antigen (CEA) was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
247
3
5

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(268 citation statements)
references
References 0 publications
12
247
3
5
Order By: Relevance
“…Such more severe lesions were more commonly observed in old animals ( Figure 1d). These features closely resembled those of PDC in humans (Carcangiu et al, 1984). However, squamoid, spindle and giant cell patterns of growth, typical of human anaplastic (undifferentiated) carcinomas, were not observed in Tg-N-ras mice.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Such more severe lesions were more commonly observed in old animals ( Figure 1d). These features closely resembled those of PDC in humans (Carcangiu et al, 1984). However, squamoid, spindle and giant cell patterns of growth, typical of human anaplastic (undifferentiated) carcinomas, were not observed in Tg-N-ras mice.…”
supporting
confidence: 62%
“…Despite its rarity, more than half of deaths attributed to thyroid cancer result from ATC (DeLellis and Williams, 2004). Follicular cell neoplasms, which, in terms of differentiation, morphology and growth, are intermediate between WDC and ATC are called 'poorly differentiated carcinomas' (PDC) (Carcangiu et al, 1984). Histological examination of PDC and ATC may also reveal WDC, which suggests that, at least in some cases, they may derive from a pre-existing WDC.…”
mentioning
confidence: 99%
“…In the present case, thyroglobulin was not detected immunohistochemically in the mononuclear cells or giant cells. However, recent immunohistochemical studies suggested that some of these tumors may stain positively for thyroglobulin (Albores-Saavedra et al, 1983;Carcangiu et al, 1985;Hurlimann et al, 1987;LiVolsi et al, 1987). These reports support this hypothesis about the origin of giant cell tumor of the thyroid.…”
Section: Discussionsupporting
confidence: 52%
“…17 Furthermore, thyroglobulin and surfactant protein are completely negative in all anaplastic thyroid carcinomas and pulmonary pleomorphic carcinomas. [18][19][20] Even the transcription factor TTF-1 is expressed only in 5.7% 21 of anaplastic thyroid carcinomas, and 55% of lung pleomorphic carcinomas. 20 The diagnosis of anaplastic carcinomas, which is the least differentiated thyroid epithelial neoplasm, is conventionally based, similarly to undifferentiated carcinomas of other organs such as upper aerodigestive tract and uterus, on: (1) a presence of differentiated thyroid carcinoma componentusually papillary carcinomas but also follicular carcinomas and poorly differentiated carcinomaswhich can be found in 50-89% of well-sampled cases; (2) involvement of the bulk of the tumor in the thyroid gland; (3) exclusion of undifferentiated tumor by metastasis or direct invasion from a neighboring organ, such as larynx.…”
Section: Discussionmentioning
confidence: 99%